Assessment of C-reactive protein, IL-6 and TNF-α Levels in Performance Enhancing-Substance (PES) Users Among Gym-Goers in Iraq (The Peerian Journal, 2025)
The use of performance-enhancing substances (PESs) across gyms and fitness communities is a growing public health concern, particularly the evidence of their potential consequences for health in both the short and long term; Objectives: The current crosssectional study was carried out between 1st of May 2024 – 4th of January 2025 to assess the levels of CRP, IL-6 as well as TNF-α among the population of gym-goers in Dyala City/Iraq. Those using PES presented significantly higher levels of CRP (5.30 ± 0.51 mg/L) when compared to non-users (1.64 ± 0.22 mg/L) (P < 0.001), showing an increased inflammatory response. Moreover, IL-6and TNF-αconcentrations were significantly increased among PES users than those non-users (55.67 ± 9.91 pg/ml vs. 40.82 ± 2.28 pg/ml, P